EFFECTIVENESS OF PRENATAL YOGA AND PREGNANCY EXERCISE TO REDUCE BACK PAIN IN 3rd TRIMESTER PREGNANT WOMEN AT PMB YANA PERMATA SARI - Yuniarsih, Yuniarsih; Futriani, Elfira Sri (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background The problem of back pain that occurs in pregnant women in the third trimester with an incidence varying from 50% in England and Australia to 70%, while in Indonesia it reaches 60-80% of 180 pregnant women who experience pain in the spine (Wulandari, 2020). This pain causes discomfort in pregnant women so there are various efforts that can be made to reduce this pain, one of which is holistic action, namely prenatal yoga and pregnancy exercise. Research purposes In general, this research aims to determine the effectiveness of prenatal yoga and pregnancy exercises to reduce back pain in pregnant women in the third trimester at PMB Yana Permata Sari. Research methods This research uses experimental research with pretest and posttest with control group type which has the characteristics of research that reveals cause and effect relationships by conducting trials on groups of research objects by making comparisons with the control group (Sujarweni, 2014). The research sample was 46 respondents with data collection techniques, namely interviews and questionnaires and data analysis techniques using bivariate and univariate tests.Research result Based on a comparison of the average value of the back pain scale from the 46 respondents, the results obtained by doing prenatal yoga reduced the level of pain by 1.48 while pregnancy exercise was only 1.18 so it was concluded that prenatal yoga was more effective in reducing the level of back pain in pregnant women in the first trimester. 3 at PMB Yana Permata Sari. Conclusions and recommendations This research concluded that prenatal yoga was more effective in reducing the level of back pain in pregnant women in the third trimester at PMB Yana Permata Sari.